Evalution of Pollution in the Hor AL –Azim Sediments by Heavy metals/ Missan Government / South of Iraq - Aufi, Aqbal (University of Thi-Qar Journal of Science, 2015)
The current study was included measurementof concentrations the coefficients of heavy elements in sediments of  casement in Hor AL-Azim reality within Hwaiza Marshes in two area Azim1 andAzim 2. measured concentrations of some heavy metals in sediments core of the study area lead, nickel, copper, Chrome and iron, appeared concentrations of values in Azim 1 (43 - 25) ppm, (32 - 170) ppm,copper (8 - 42) ppm and (50 - 139) ppm and (2593 – 8675) ppm respectively. Also been identified coefficient assembly geochemical heavy metals, which was in Azim 1 for lead ,nickel,copper,Chrome,iron between(0.357 - 0.585) ,( 0.076 - 0.383) ,(0.026 - 0.14) ,(0.098 - 0.272) and (9.211 - 30.809) respectively, either in Azim 2 for the same metals (0.4 - 0.642) ,( 0.071 - 0.338) ,(0.02 - 0.083) ,(0.098-0.231) and (7.48 - 25.62) respectively. Also determined the coefficient enrichment of heavy metals in the sediments of Azim 1 for lead ,nickel,copper,Chromebetween (0.016 - 0.053) ,(0.0031 - 0.0325) , (0.001-0.014) and(0.003-0.019) respectively and Azim 2 for the same metals between (0.019 - 0.054) ,( 0.00413-0.025) ,(0.0012 -0.0089) and (0.00320.013) respectively. Identified Concentration Factor of the heavy metals in the Azim 1 for lead ,nickel,copper,Chrome,iron between(1.785-3.071) ,(0.38 -2.023) ,(0.7-0.133), (0.49-1.362) and (46.056 - 154.04) andAzim 2 for the same metals between (2-3.214) ,(0.357 -1.69) ,(0.1-0.416) ,( 0.49-1.156) and (37.424 - 128.11)respectively.